Desarrollo e implementación de un proyecto de Software Libre con entorno WEB para Cooperativas de Ahorro y Crédito, orientado a Asociaciones de Precooperativa de Ahorro y Crédito Kiskinchir, Caja Solidaria Ñauparina del Cantón Saraguro de la Provincia de Loja. - Ortega Ambuludí, José Claudio (2011)
This research project was undertaken with the purpose of developing a web environment free software for credit unions, associations "PRE-COOPERATIVA DE AHORRO Y CRÉDITO KISKINCHIR” and "CAJA SOLIDARIA ÑAUPARINA” from city Saraguro of the province Loja taking into account that it is a very extensive project has been taken into account the primary parts such as associates management, accounts, investments and loans. For the development of the project has used free software, starting as a programming language PHP, Symfony as a framework, Netbeans ID as editor code, FPDF to generate PDF files, Git as version control, github as repository software, Mysql as database manager, and Propel as ORM for PHP5, and Apache as web server.